Socio-Pedagogical Prevention of Bullying in the School Environment: A Gender-Oriented Approach - Myrzapeissova , Meruyert; DUDA , EWA (Pedagogy and Psychology, 2025)
The article examines the socio-pedagogical prevention of bullying among schoolchildren, with special consideration of gender-specific behavioral characteristics. Bullying is a widespread phenomenon that threatens children’s safety, well-being, and academic achievement. Research shows that boys are more frequently involved in physical and direct bullying, while girls tend to use relational and indirect forms such as exclusion or rumor-spreading. In Kazakhstan, similar tendencies are observed, underscoring the need for gender-sensitive prevention programs. Methodology and Methods. The study is based on a literature review of both classical and contemporary scholarly works, including international and Kazakhstani research. The analysis covers psychological, family, school, and peer-related factors influencing bullying, with particular attention to the role of gender norms in shaping aggressive and victimized behaviors. Results. The findings indicate clear gender differences: boys are more prone to overt physical and verbal bullying, whereas girls more often use relational and indirect forms. Cyberbullying affects both genders almost equally, although girls are slightly more often victims. The school climate, teacher attitudes, family conditions, and peer norms strongly determine the forms and prevalence of bullying. Scientific novelty. The research develops a socio-pedagogical model of bullying prevention that incorporates gender-specific behavioral patterns. The study demonstrates the importance of differentiated prevention strategies for boys and girls to enhance the effectiveness of anti-bullying programs. Practical significance. The proposed approach can be applied in schools to strengthen preventive work, improve the socio-psychological climate, and enhance cooperation among teachers, students, and parents. It provides practical recommendations for reducing aggression, addressing cyberbullying, and fostering safe and supportive school environments where every child feels valued.